Effect of ultraviolet irradiation on the osseointegration of a titanium alloy with bone - Ashish Yadav; Ranjana Yadav; Aratee Gupta; Akash Baranwal; Atul Bhatnagar; Vakil Singh (Wolters Kluwer Medknow Publications, 2017)
Introduction: Attempt has been made to analyze the potential of titanium (Ti) alloy for osteointegration by the effect of surface photo functionalization in different aspects as follows: in Ringer's solution, in vitro cell growth, and in vivo study on rabbit. The present study was aimed to investigate the influence of ultraviolet (UV) light on surface topography, corrosion behavior, and bioactivity of indigenously manufactured samples of Ti alloy mini-implant. Materials and Methods: The study includes surface modification of Ti samples by UV treatment, corrosion testing of the specimens using Potentiostat (GAMRY System), qualitative examination of modified surface topography using scanning electron microscope, and cellular viability test on Ti alloy surface (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide ASSAY). To find the effect of UV light on implant bone integration, biochemical test was performed on the femur of rabbits. Results and Discussion: Corrosion resistance of untreated Ti alloy in Ringer's solution was found to be less, whereas corrosion rate was more. Corrosion resistance of UV-treated samples was found to increase significantly, thereby lowering the corrosion rate. Cell growth in UV-treated specimen was observed to be higher than that in untreated samples. It is important to mention that cell growth was significantly enhanced on samples which were UV treated for longer duration of time. Conclusions: There was a marked improvement in cell growth on UV-treated Ti alloy samples. Hence, it is expected that it would enhance the process of osseointegration of Ti with bone. Another important finding obtained was that the removal torque values of UV-treated implants were higher than that of untreated implants. The overall result reveals that UV treatment of implants does help us in speeding up the osseointegration process.